If it's not what You are looking for type in the equation solver your own equation and let us solve it.
a+4/3=6
We move all terms to the left:
a+4/3-(6)=0
determiningTheFunctionDomain a-6+4/3=0
We multiply all the terms by the denominator
a*3+4-6*3=0
We add all the numbers together, and all the variables
a*3-14=0
Wy multiply elements
3a-14=0
We move all terms containing a to the left, all other terms to the right
3a=14
a=14/3
a=4+2/3
| -5t-8=9t+8 | | 3v+-5v=12 | | 34=6(1-4x)-4(1+2x) | | 7(b-4)-4(1-4b)=37 | | -6r-4=8 | | 2(z-5)=16 | | -6(8a+7)+6a=1+a | | 9x=10x-18 | | 19r-9r+2=-18 | | 72=5x+8+8x-1=72 | | -15=-5/2y | | 3(2-3h)=7 | | 8(1+3x)=40+8x | | 7-2(5x-4)=-5 | | 4v=6+5v | | 40+2x=60+3x | | 18-15w+7w-4=28 | | (15x+5)=(6x+6)+80 | | -3(5x-5)=5(2-3x)+5 | | 2(d-18)=-4 | | 3m+(2m+6)=5m | | 3+(b+8)=3(8+b) | | -5/2+6/5v=-5/3 | | )5x-3+6(x+1)=-2x+5 | | 6p+5p+5=-8-2p+24 | | -9h=6-6h | | -12=-4(v+11) | | 270=100-u | | (13x-3)=(3x+2)+55 | | 0.2(7+2t0=0.4t+1.4 | | 3d-2d-1=11 | | 5(t+2)-(3t-2)=4(3t+1)-12 |